2004
DOI: 10.1161/01.cir.0000143624.72027.11
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factors in the Collateral Circulation of Chronic Total Coronary Occlusions

Abstract: In CTOs, the continuous release of bFGF into collaterals showed a close relation to the duration of occlusion and collateral function, which underscores its therapeutic potential. Other factors influencing growth factor release appeared to be shear stress for MCP-1, TGF-beta, and PlGF and the presence of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 43 publications
3
29
1
2
Order By: Relevance
“…In case of severe stenosis, the pressure difference between coronary artery with Data are presented as mean±SD *t-test for independent samples ALT -alanine aminotransferase; AST -aspartate aminotransferase; hs-CRP-C-reactive protein; GGT -gamma-glutamyltransferase; UA -uric acid; WBC -white blood cell severe stenosis and normal coronary artery increases blood flow of the embryonic arterial network and activates certain growth factors and endothelial cells, which facilitates the opening of collateral vessels (26). Many clinical studies have demonstrated a positive association between plasma growth factors and the presence of collaterals (7,27). Chronic hypoxia leads to the activation of both angiogenesis and arteriogenesis resulting in the collateral vessels to restore blood flow to the ischemic territory (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of severe stenosis, the pressure difference between coronary artery with Data are presented as mean±SD *t-test for independent samples ALT -alanine aminotransferase; AST -aspartate aminotransferase; hs-CRP-C-reactive protein; GGT -gamma-glutamyltransferase; UA -uric acid; WBC -white blood cell severe stenosis and normal coronary artery increases blood flow of the embryonic arterial network and activates certain growth factors and endothelial cells, which facilitates the opening of collateral vessels (26). Many clinical studies have demonstrated a positive association between plasma growth factors and the presence of collaterals (7,27). Chronic hypoxia leads to the activation of both angiogenesis and arteriogenesis resulting in the collateral vessels to restore blood flow to the ischemic territory (28).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic ischemic heart disease and similar degrees of coronary artery stenosis exhibit marked variability in the presence of spontaneously visible collaterals, but the biological basis of this heterogeneity is not known (5). Studies have suggested that growth factors and healthy endothelium are important for development of collateral vessels (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Werner et al, in 104 patients with chronic total coronary occlusion, the FGF2 concentration in the collateralized arteries was higher than in the aortic root. 16 FGF2, its concentrations highest in recent occlusions (2 to12 weeks), which have the highest collateral resistance index, is the only growth factor that exhibits a close relation to the duration of occlusion and collateral function. 16 FGF2 does not have a role in producing immature vessels with increased permeability, although that does not exclude VEGF's participation in establishing a new vascular network that includes capillaries.…”
mentioning
confidence: 95%
“…16 FGF2, its concentrations highest in recent occlusions (2 to12 weeks), which have the highest collateral resistance index, is the only growth factor that exhibits a close relation to the duration of occlusion and collateral function. 16 FGF2 does not have a role in producing immature vessels with increased permeability, although that does not exclude VEGF's participation in establishing a new vascular network that includes capillaries. Both FGF2 and VEGF are known for their ability to promote endothelial cell proliferation and migration and to stimulate tube formation by means of activation of the phosphatidylinositol 3-kinase/Akt signaling pathway.…”
mentioning
confidence: 95%
“…Fibroblast growth factor (FGF)2, whose participation in CD133 ϩ cell-related Wnt signaling is not discussed in the present study, is more closely related to compensatory vasculogenesis. 17 Because FGF2 and VEGF are both critical to tissue repair, 13 it is important to examine how diabetes mellitus modulates angiogenic activities regulated by these growth factors.…”
mentioning
confidence: 99%